Penerapan Media Video Interaktif Berbasis Edpuzzle dalam Meningkatkan Motivasi dan Hasil Belajar Siswa di SDN Kejapanan 4 Pasuruan - Zariyatus Sholikhah; M. Anang Solikhudin; M. Nur Hadi; Achmad Yusuf; Ahmad Ma’ruf (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Education in the digital era faces new challenges in enhancing student motivation and learning outcomes. An intriguing alternative to explore is the use of interactive video media based on Edpuzzle in the teaching process. However, research specifically investigating the implementation of Edpuzzle in enhancing student motivation and learning outcomes at the elementary school level is still limited. The aim of this research is to understand the implementation, supporting factors, barriers, and impacts of using Edpuzzle in enhancing student motivation and learning outcomes at SDN Kejapanan 4 Pasuruan. The research methodology employed is a qualitative approach with a descriptive qualitative type. Data collection was conducted through interviews with Islamic education teachers, direct observations, and documentation. Data gathering techniques included observation, interviews, and documentation. The collected data were then analyzed using qualitative data analysis techniques. The results of the research indicate that the implementation of Edpuzzle has successfully increased student motivation and learning outcomes at SDN Kejapanan 4 Pasuruan. It was found that the main supporting factors in the implementation of Edpuzzle are adequate technological infrastructure and support from the school, while the main barriers are the limitations of devices in the school and unstable internet access for some students at home. The positive impact of using Edpuzzle includes increased student engagement in learning and improved understanding of the material. Therefore, the use of interactive video media based on Edpuzzle can be an effective model in enhancing student motivation and learning outcomes at the elementary school level.